Adding Pay-for-Performance Program to Routine Care Was Related to a Lower Risk of Depression Among Type 2 Diabetes Patients in Taiwan - Lian, Wei-Cheng; Livneh, Hanoch; Huang, Hui-Ju; Lu, Ming-Chi; Guo, How-Ran; Tsai, Tzung-Yi (Frontiers in Public Health, 2021)
Background: Patients with type 2 Diabetes (T2DM) often experience depression during treatment, negatively influencing their treatment compliance and clinical outcomes. Recently, the pay-for-performance (P4P) program for chronic diseases, with high-cost and high-risk feature, such as T2DM, has been implemented and has been operational for several years. Nevertheless, its effect on the risk of developing depression among T2DM cases is unknown. This study aims to explore the association of P4P use with the subsequent risk of developing among these groups. Methods: This cohort study used a nationwide health insurance database to identify patients 20–70 years of age newly diagnosed with T2DM who enrolled P4P between 2001 and 2010. From this group, we enrolled 17022 P4P users and 17022 non-P4P users, randomly selected using propensity-score–matching. Enrolled patients were followed until the end of 2012 to record the occurrence of depression. The Cox proportional hazards regression model was utilized to obtain the adjusted hazard ratio (aHR) for P4P use. Results: During the study period, a total of 588 P4P users and 1075 non-P4P users developed depression at incidence rates of 5.89 and 8.41 per 1000 person-years, respectively. P4P users had a lower depression risk than did non-P4P users (aHR, 0.73; 95% Confidence Interval, 0.65–0.80). This positive effect was particularly prominent in those receiving high-intensity use of the P4P program. Conclusion: Integrating P4P into routine care for patients with T2DM may have beneficial effects on curtailing the sequent risk of depression.